Environmental magnetism study during the Mid-Late Holocene transition and its cultural implications in Mesoamerica. (10th March 2021) - Wogau, Kurt H.; Nowaczyk, Norbert R.; Böhnel, Harald N.; Arz, Helge W.; Molina-Garza, Roberto
Abstract: In the Mesoamerican region, arid or hydrological variable conditions are commonly interpreted from 4 ka onwards. It is not well known how these changes modified the Mesoamerican monsoon system, which were the main atmospheric-oceanic forcings involved and their effect in the Pre-Classic Mesoamerican societies' history. Here, we study the possible link between paleoclimatic changes and decreased social development of societies in Mesoamerica during the Pre-Classic period (4.3 ka to 2.2 ka), which correspond to the Middle-Late Holocene transition. We also describe the principal oceanic-atmospheric mechanism related. We employed a partly laminated sediment sequence from La Alberca maar lake in the central Mexico highlands by means of environmental magnetism and comparing versus X-ray fluorescence (XRF), pollen, and δ 18 O analyses. Increased concentrations and preservation of ferrimagnetic minerals and enhanced detrital load as described by the XRF Ti counts reveal the occurrence of variable hydrological conditions between 4.4 ka to 2.2 ka. These conditions coincide with the onset of high-frequency latitudinal variations of the Intertropical Convergence Zone (ITCZ) and the rise of ENSO and Pacific decadal oscillation activity. We suggest that variable hydrological conditions affected the development of Mesoamerican agrarian societies stressing agricultural production during the Pre-Classic period. Highlights: The magnetic mineralogy and derived parameters from La Alberca maar lake recorded highly variable hydrological conditions between 4.4-2.2 ka. Decadal precipitation events produced oxic conditions, thus increasing the concentration and preservation of the ferrimagnetic fraction. Variable hydrological conditions in La Alberca lake between 4.4-2.2 ka correlates with the high frequency latitudinal variations of the ITCZ. The variable hydrological conditions hindered the adaptation of early Pre-Classic Mesoamerica cultures to the natural environment and resources.